Hubungan Health Literacy dengan Perilaku Mencari Bantuan Kesehatan - Anwar, Mardiana; Irwan, Andi Masyita; Syam, Yuliana (Jurnal Keperawatan Muhammadiyah, 2019)
Background: Health literacy is defined as the degree to which individuals have the ability to obtain, process, and understand the basic health information and resources needed to make the right decisions. The highest prevalence of health literacy is low in individuals with low education, minority status, parents, and people with low cognitive abilities. Therefore, the higher the health literacy possessed by someone, the more active they will be in seeking health assistance.Objective: of this literature study is to analyze the correlation between health literacy and health-seeking behavior.Method: The data bases in making this literature review is Pubmed, Google Scholar and Science Direct. The keywords used in article search are "health literacy" and "health- seeking behavior." Then filter the last 6 years, full text and selected according to the appropriate literature study topic.Results: Based on the results of a literature search of 39 articles obtained, there were 5 articles that met the criteria. The study looked at the relationship between health literacy and health-seeking behavior.Conclusion: health literacy influences individual behavior in seeking health assistance